Cistoplastia com peritônio autólogo em cães - Daleck, Cintia Lucia Maniscalco; Daleck, Carlos Roberto; Padilha Filho, João Guilherme (Semina: Ciências Agrárias, 1989)
<!--[if gte mso 9]> Normal 0 21 MicrosoftInternetExplorer4 <![endif]--><!--[if !mso]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> 10 male dogs, of undefined breeding, were used to study the viability of autologous peritoneum in substitution of a urinary bladder segment. In the pre and post operative phases, the dogs were submitted to various laboratory exames (urine: physical, chemical and blood: eritrograma and urea) plus radiology and body temperature. The time of observation ranged from 1.5 to 120 days. The hystologic aspect showed a bone metaplasia in the site of the implants.